Brain computer interface based smart keyboard using neurosky mindwave headset - Thair A. Salih; Yasir M. Abdal (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
In the last decade, numerous researches in the field of ‎electro-encephalo-graphy (EEG) and brain-computer-interface ‎‎(BCI) have been accomplished. BCI has been developed to aid ‎disabled/partially disabled people to efficiently communicate ‎with the community. This paper presents a control tool using ‎the Neurosky Mindwave headset, which detects brainwaves ‎‎(voluntary blinks and attention) to form a brain-computer ‎interface (BCI) by receiving the system signals from the frontal lobe. This paper proposed an alternative computer input device ‎for those disabled people (who are physically challenged) ‎rather than the conventional one. The work suggested to use ‎two virtual keyboard designs. The conducted experiment ‎revealed a significant result in developing user printing skills ‎on PCs. Encouraging results (1.55-1.8 word per minute ‎‎(WPM)) were obtained in this research in comparison to other ‎studies.